A Cross-sectional study of glycosylated hemoglobin in different trimesters of normal pregnancy. - Dr . Archana; Kamal , Anil Kumar; Arora, Ranjit Kumar; Shrivastava, Priyanka; Kumar, Deepak; Rajak, Ranjit Kumar; Kumari, Madhu (Student’s Journal of Health Research Africa, 2025)
Background Glycated hemoglobin (HbA1c) is widely accepted as a reliable indicator of long-term glycemic control. Unlike oral glucose tolerance tests (OGTT), which are the standard diagnostic tool for gestational diabetes mellitus (GDM) but often poorly tolerated during pregnancy, “HbA1c testing offers a non-fasting, convenient, and stable measure of blood glucose control over the previous 2–3 months. This study aims to assess the physiological variations in HbA1c levels across different trimesters of normal pregnancy in comparison with non-pregnant women of the same age group. Methods The study was conducted at the Department of Physiology, RIMS, Ranchi, from January 2016 to February 2017. A total of 60 female subjects, aged between 18 and 30 years, were included: 15 non-pregnant women (controls) and 45 pregnant women, distributed equally across the three trimesters. HbA1c levels were measured using the High-Performance Liquid Chromatography (HPLC) method. Statistical analysis was performed using MedCalc software to determine the significance levels between groups. Results The mean HbA1c level in non-pregnant women was 5.55% ± 0.30, which was higher than in all trimesters of pregnancy. In the first, second, and third trimesters, the mean HbA1c levels were 5.12% ± 0.32, 5.33% ± 0.32, and 5.03% ± 0.28, respectively. A significant reduction in HbA1c was observed in the first and third trimesters compared to the non-pregnant group (p = 0.0007 and p < 0.0001, respectively). The increase in the second trimester was not statistically significant when compared to the first. Conclusion HbA1c levels fluctuate during pregnancy due to physiological changes and should be interpreted with trimester-specific references. These findings support the potential utility of HbA1c as a complementary tool for glycemic assessment during pregnancy. Recommendation Clinicians consider using trimester-specific HbA1c reference ranges in routine prenatal care to improve monitoring of maternal glycemic status, especially when OGTT is not feasible.